Optimization of tensile strength in 3D printed PLA parts via meta-heuristic approaches: a comparative study - Jatti, Vijaykumar S.; Tamboli, Shahid; Shaikh, Sarfaraj; Solke, Nitin S.; Gulia, Vikas; Jatti, Vinaykumar S.; Khedkar, Nitin K.; Salunkhe, Sachin; Pagáč, Marek; Abouel Nasr, Emad S. (Frontiers in Materials, 2024)
This research focuses on the relationship between the tensile strength of PLA material and several 3D printing parameters, such as infill density, layer height, print speed, and extrusion temperature, utilizing the Fused Deposition Modelling (FDM) method of Additive Manufacturing (AM). Tensile strength of the samples was determined in compliance with ASTM D638 standard, and the experiments were carried out according to a planned arrangement. Six distinct methods were used to optimize the tensile strength: Particle Swarm Optimization (PSO), Teaching Learning Based Optimization (TLBO), Genetic Algorithm (GA), Simulated Annealing (SA), and Cohort Intelligence (CI). Several runs of the optimization methods demonstrated their consistency in producing the same values of tensile strength, indicating their reliability. The optimization resultsshowed that JAYA performed better than the other algorithms, resulting in a material with the maximum tensile strength of 55.475 N/mm 2 . Validation experiments were carried out to confirm the efficacy of these algorithms. The results showed that the ideal input parameters produced tensile strength values that closely matched the anticipated values with a low percentage error. The benefits of applying these algorithms to improve the tensile strength of PLA materials for 3D printing are demonstrated by this study, which also offers insightful information about how to optimize FDM procedures.